Evaluation of efficacy of palonosetron versus ramosetron in patients receiving emetogenic chemotherapy - Ghazala, Zainab; Kalshetty, Prakash; V., Anuradha H. (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Chemotherapy induced nausea and vomiting is the most distressing side effect of cancer chemotherapy. It can seriously impact patient’s quality of life, influence the adherence to chemotherapy and progression free survival causing a delay or refusal of potentially life-saving therapy. The objective of this study was to compare the efficacy of palonosetron with ramosetron in achieving complete response to the chemotherapy. Methods: This was a prospective randomized open-label study conducted on 130 patients admitted in Medical Oncology ward of a Tertiary Care Hospitals, Bangalore, India. Patients were randomized to receive either palonosetron 0.25 mg or ramosetron 0.3 mg I.V. along with aprepitant and dexamethasone 30 minutes prior to chemotherapy and were followed up for a period of 5 days post chemotherapy. The observations such as number and severity of vomiting and nausea, the outcome was assessed at the end of 5 days. Pearson’s Chi-square test was used to demonstrate the difference between both the study groups with respect to various categorical data. Results: The complete response rate in delayed phase was more significant in patients who received palonosetron than patients who received ramosetron (72.3% vs 50.8%). Total control was achieved in 38.5% patients with palonosetron as compared to 15.4% patients with ramosetron. Conclusions: Palonosetron is more efficacious than ramosetron in controlling chemotherapy induced nausea and vomiting especially in delayed phase of emesis.